Pengaruh Reward Kerja, Stres Kerja, Motivasi Kerja, dan Kepuasan Kerja terhadap Loyalitas Karyawan Divisi Marketing pada PT Pilar Bangun Kencana Surabaya - Zein, Selina Ashilah; Nirawati, Lia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The development and competition of the property business are getting tighter because the construction of apartments is more than housing. The employee loyalty factor is crucial for the continuity and success of the company in the long term. Factors influencing it are needed to achieve high employee loyalty, such as work rewards, work stress, motivation, and job satisfaction. This study aims to determine the influence of Work Reward, Work Stress, Work Motivation, and Job Satisfaction on Employee Loyalty in the marketing division of PT Pilar BangunKencana Surabaya. This type of research is quantitative research, while the population in this study were all employees of PT Pilar BangunKencana, totalling 83 people, and the sample of this study was 47 marketing division people with sampling techniques, purposive sampling. Data analysis was performed using the IBM SPSS 24 program. The results of this study, it is concluded that Work Reward, Job Stress, Work Motivation, and Job Satisfaction simultaneously have a significant effect on Employee Loyalty with a sig value of 004<0.05 and F-count>Ftable (4.513>2.59). Work Reward partially has no significant impact on Employee Loyalty with a sig value of 0.674>0.05 and t-count<t-table (0.423<2.018). Job Stress partially has a negative and significant effect on Employee Loyalty with a sig value of 0.011<0.05 and t-count>t-table -2.647>-2.018. Work Motivation partially has no significant impact on Employee Loyalty with a sig value of 0.074<0.05 and t-count>t-table 1.833>2.018. Job Satisfaction partially has a positive and significant effect on Employee Loyalty with a sig value of 0.043<0.05 and t-count>t-table 2.085>2.018. Keywords: Work Reward, Work Stress, Work Motivation, Job Satisfaction, Employee Loyalty